Mediation effect of stroke recurrence in the association between post-stroke lactate dehydrogenase and functional disability - He, Qian; Wang, Miaoran; Zhu, Haoyue; Xiao, Ying; Wen, Rui; Liu, Xiaoqing; Shi, Yangdi; Zhang, Linzhi; Wang, Yu; Xu, Bing (Frontiers in Aging Neuroscience, 2024)
Background We aimed to use lactate dehydrogenase (LDH) as a marker of inflammation burden and quantify post-stroke inflammation’s direct and indirect effect on functional disability. Methods We analyzed 5,129 patients with acute ischemic stroke (AIS) admitted to Shenyang First People’s Hospital. Stroke recurrence and functional outcome measured by the modified Rankin Scale (mRS) were assessed at 90 days. Functional disability was defined as mRS score > 2. Receiver operating characteristic curve and restricted cubic spline (RCS) analysis were conducted to illustrate the associations between LDH levels and 90-day functional outcomes in patients with AIS. Mediation analyses were performed to examine the potential causal chain in which stroke recurrence may mediate the relationship between LDH and functional outcome. Positive correlation between LDH and hs-CRP was found and mediation effects of stroke recurrence in the association between LDH or hs-CRP and functional disability were both less than 20%. Sensitivity analyses in different subgroups showed comparable results. Results Among 5,129 included AIS patients, the median (IQR) level of LDH was 186 (161–204.4) U/L. Functional disability was seen in 1200 (23.4%) patients and recurrence was observed in 371(7.2%) patients at 90-day follow-up. Each standard deviation increase in the concentration of LDH was linked to an increased risk of functional disability (adjusted odds ratio[aOR], 1.07; 95%CI,1.04–1.09) and stroke recurrence (aOR,1.02; 95%CI, 1.01–1.04) within 90 days. The highest quartile of LDH (>204.2 U/L) had an elevated risk of suffering functional disability (aOR, 1.21; 95%CI, 1.00–1.47) and recurrence (aOR, 1.21; 95%CI,1.00–1.47) compared with the lowest quartile of LDH (<161 U/L). Stroke recurrence during follow-up explained 12.90% (95%CI, 6.22–21.16%) of the relationship between LDH and functional disability. Positive correlation between LDH and hs-CRP was found and mediation effects of recurrence in the association between LDH or hs-CRP and functional disability were both less than 20%. Sensitivity analyses in different subgroups showed comparable results. Conclusion The relationship between LDH and functional disability at 90 days among AIS patients is partially mediated by stroke recurrence, accounting for less than 20%. LDH deserves equal attention as hs-CRP in predicting recurrence and functional outcome. In addition to traditional secondary prevention measures, innovative anti-inflammatory strategies warrant further investigation.